2014
DOI: 10.1177/0956797613511468
|View full text |Cite
|
Sign up to set email alerts
|

Feeling the Conflict

Abstract: In the study reported here, we examined the role of conflict experience in cognitive adaptation to conflict. Although the experience of conflict is generally neglected in theoretical models of cognitive control, we demonstrated that it plays a critical role in cognitive adaptation. Using a masked-priming paradigm, we showed that conflict adaptation was present only after trials on which participants experienced response conflict. Furthermore, when subjective experience did not coincide with actual conflict, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 34 publications
8
58
0
Order By: Relevance
“…They explained their results by a meta-cognitive process: they assumed that subjects were aware of the consequences of the high proportion of incongruent trials (higher number of errors) and regulated their behavior accordingly, even though they were not aware of the conflict itself. This interpretation fits with the idea that masked stimuli cannot trigger cognitive control directly, but that the reportable consequences of these stimuli can [11,66,67]. Note that the priming effects in Jáskowski et al’s study are very strong (about 100 ms difference in reaction times and about 15% error rate in incongruent trials), allowing subjects to notice changes in these parameters.…”
Section: Discussionsupporting
confidence: 72%
“…They explained their results by a meta-cognitive process: they assumed that subjects were aware of the consequences of the high proportion of incongruent trials (higher number of errors) and regulated their behavior accordingly, even though they were not aware of the conflict itself. This interpretation fits with the idea that masked stimuli cannot trigger cognitive control directly, but that the reportable consequences of these stimuli can [11,66,67]. Note that the priming effects in Jáskowski et al’s study are very strong (about 100 ms difference in reaction times and about 15% error rate in incongruent trials), allowing subjects to notice changes in these parameters.…”
Section: Discussionsupporting
confidence: 72%
“…Gratton, Coles, and Donchin (1992) first reported that the compatibility effect is smaller when the previous flanker trial is incompatible versus compatible, a finding that since has been replicated many times (for reviews, see Clayson & Larson, 2013;Verguts & Notebaert, 2008). The dominant explanation for this phenomenon is that the experience of conflict-particularly when conflict is aversive (see Desender, Van Opstal, & Van den Bussche, 2014;Driesbach & Fischer, 2015;Inzlicht, Bartholow, & Hirsch, 2015;Steenbergen, Band, & Hommel, 2009)-elicits adjustments in cognitive control so that subsequent conflict can be better managed-a so-called conflict adaptation effect. 1 This explanation accords with dominant theories emphasizing the dynamic interplay of conflict monitoring, attention control, and response implementation.…”
Section: Introductionmentioning
confidence: 96%
“…That is, conflict produces a subjective experience that is aversive, and thereby triggers adjustments in control that serve to counter the negative affect (see Dreisbach & Fischer, 2011, for important evidence showing that conflict-free, disfluent stimuli are also aversive and trigger such control adjustments; cf. Desender, Van Opstal, & Van den Bussche, 2014, who found that the subjective experience of conflict drives control adjustments underlying the congruency sequence effect). This is pertinent to the present findings because pupillometry appears to be well suited to detecting changes in affective experience (see Chiesa, Liuzza, Acciarino, & Aglioti, 2015 for evidence that pupillometry is even sensitive to subliminally presented affect primes).…”
Section: Discussionmentioning
confidence: 99%